2006
DOI: 10.1037/0735-7028.37.3.317
|View full text |Cite
|
Sign up to set email alerts
|

Nature and severity of college students' psychological concerns: A comparison of clinical and nonclinical national samples.

Abstract: counseling center staff members have expressed a growing concern about the perceived increasing severity of college students' presenting problems. The main goal of this study was to explore the nature and severity of college students' presenting problems by establishing a baseline measure. The research summarized here was derived from 3 large-scale studies involving 1 nonclinical and 2 clinical samples surveyed by counseling centers that were members of the Consortium of Counseling Psychological Services in Hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
70
0
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(79 citation statements)
references
References 9 publications
5
70
0
4
Order By: Relevance
“…8,13,14 In other studies, the complaints mainly comprise problems in the field of interpersonal relationships and worries about academic and career-related issues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,13,14 In other studies, the complaints mainly comprise problems in the field of interpersonal relationships and worries about academic and career-related issues.…”
Section: Discussionmentioning
confidence: 99%
“…13,14,17 Although they may be few in number, students with serious mental health illness or psychological problems are highly demanding in terms of staff time and resources and they are especially challenging to campus mental health services. 2,15 A recent study suggested that campus mental health services can possibly reduce the delay between the onset of psychiatric conditions and its proper treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the development of the mental health of students over time, there are several studies showing an increase in mental health problems of students [10,43]. Such a development is also evident on data concerning the demand for consultation at counseling services for students.…”
Section: Current Data On Mental Health Of Students Internationallymentioning
confidence: 91%
“…(Erdur-Baker, Aberson, Barrow, & Draper, 2006) and to address those students with psychosocial problems. This may help in utilization of mental health services for vulnerable students.…”
Section: Discussionmentioning
confidence: 99%